Pengabdian Kepada Masyarakat Pendampingan Dan Transformasi Umkm Zhofi Melalui Pendekatan Terpadu Pengembangan Usaha: Community Service Assistance and Transformation of Zhofi MSMEs Through an Integrated Business Development Approach - betri betri sirajuddin; Maidiana Astuti Handayani; Ida Zuraidah; M. Amien Dwi Putra (Universitas Muhammadiyah Palembang, 2025)
MSMEs in Indonesia play a strategic role in supporting economic growth and job creation, but they still face various structural challenges. This prevents many MSMEs from optimally transforming in the digital era. This programme aims to provide assistance and encourage the transformation of the Zhofi handmade bag MSME through an integrated business development approach, including production, marketing, capitalisation, technology enhancement, and financial management. The programme was conducted from September to December at the Zhofi MSME in Talang Kelapa, Alang-alang Lebar District, Palembang City. Challenges faced included production management, digital marketing, financial record keeping, and access to capital. Activities included needs identification, field observation, training, implementation, and evaluation. This programme successfully increased production efficiency, strengthened digital marketing strategies, improved financial records, and increased MSME readiness to utilise technology and access financing. Results show that the integrated approach significantly improved MSME performance and served as a business development model for other MSMEs facing similar challenges. This transformation reflects the importance of sustainable mentoring in increasing MSME competitiveness in the digital era.